The Propensity for Inducing Atrial Fibrillation: A Comparative Study on Old versus Young Rabbits. (1st March 2014) - Li, Hongliang; Scherlag, Benjamin J.; Kem, David C.; Zillner, Caitlin; Male, Shailesh; Thirunavukkarasu, Sorkko; Shen, Xiaohua; Benbrook, Alexandria; Pitha, Jan V.; Lazzara, Ralph; Yu, Xichun
Abstract : It is well established that atrial fibrillation (AF) is far more common in elderly humans. Autonomic activation is thought to be an operative mechanism for AF propensity. The aim of the study was to investigate the impact of age on atrial tachyarrhythmia induction in a rabbit model. Six old (aged 4–6 years) and 9 young (aged 3-4 months) New Zealand white rabbits were subjected to a catheter-based electrophysiological study. Atrial tachyarrhythmia susceptibility was tested by burst pacing before and after infusion of increasing concentrations of acetylcholine. Both young and old rabbits were in normal sinus rhythm at the beginning of the infusion/burst pacing protocol. The old rabbits had faster heart rates and a marked increase in atrial tachyarrhythmias compared to the young rabbits. Nonsustained and sustained AF events were more frequent in the old rabbits. No significant fibrosis was observed in the atria of either young or old rabbits. In conclusion, the old rabbits have a greater propensity for induction of AF. The significantly faster heart rates in the old rabbits suggest that dominant sympathetic activity may play an important role in the propensity for AF in this group.